KOMPETENSI GURU DALAM MELAKSANAKAN PENILAIAN AUTENTIK DI MADRASAH ALIYAH NEGERI (MAN) PULANG PISAU KABUPATEN PULANG PISAU KALIMANTAN TENGAH - Gito Supriadi Gito (Jurnal Evaluasi Pendidikan, 2021)
The objectives of this study are (1) to describe teacher competency in implementing authentic assessments in the realm of attitudes, (2) to describe teacher competency in implementing authentic assessments in the realm of knowledge, and (3) to describe teacher competency in the authentic assessments in the realm of skills. The approach that used in this research is quantitative approach. Meanwhile, the sample that used in this research is saturation sampling technique with a sample of 22 teachers at MAN Pulang Pisau. Whereas, questionnaire with the Guttman scale is the data collection techniques that used in this research. Thus, the researcher used descriptive statistics as the data analysis. The results showed that: (1) Teacher competency in implementing authentic assessments in the realm of attitude at MAN Pulang Pisau obtained an average percentage of 43.75%, with a sufficient category. (2) The competency of teachers in implementing authentic assessments in the realm of knowledge at MAN Pulang Pisau obtained an average percentage of 89.61%, with a very good category. Lastly, (3) Teacher competency in implementing authentic assessments in the realm of skills at MAN Pulang Pisau obtained an average percentage of 68.18%, with a good category. Keywords: competency, assessment authentic